Comparative study on Cronobacter sakazakii and Pseudomonas otitidis isolated from septic tank wastewater in microbial fuel cell for bioelectricity generation. (15th July 2019) - Thulasinathan, Boobalan; Nainamohamed, Samsudeen; Ebenezer Samuel, James Obeth; Soorangkattan, Saravanan; Muthuramalingam, JothiBasu; Kulanthaisamy, Mohanrasu; Balasubramani, Ravindran; Nguyen, Dinh Duc; Chang, Soon Woong; Bolan, Nanthi; Tsang, Yiu Fai; Amabilis-Sosa, Leonel Ernesto; et al.
Graphical abstract: Highlights: Bioelectricity generation from septic tank wastewater in MFC was investigated. Cronobacter sakazakii and Pseudomonas otitidis were isolated and identified using 16S rRNA gene sequences. Isolated species were tested as a biocatalyst in MFC for energy generation. P. otitidis AATB4 produced higher power density at pH 7 than C. sakazakii AATB3. P. otitidis AATB4 produced maximum power at pH 7 than at pH 6 and 8. Abstract: The potential of microbial isolates from septic tank wastewater to generate bioelectricity in microbial fuel cell was investigated. The isolates were identified as Cronobacter sakazakii AATB3 and Pseudomonas otitidis AATB4. The sterilized septic tank wastewater alone was used as an organic matter to study the exact role of the isolates in bioelectricity production and biodegradation of septic tank wastewater. P. otitidis AATB4 achieved the highest bioenergy generation (i.e., power density of 280 mW/m 2 and current density of 800 mA/m 2 ), highest COD removal (i.e., 79.1%), and maximum coulombic efficiency of 15.5% at pH 7. The biofilm of P. otitidis AATB4 at the anodic surface contained 49 µg/cm 2 of protein and 57 µg/cm 2 of carbohydrate. Scanning electron microscope and confocal laser scanning microscope revealed 46 µm biofilm thickness by P. otitidis AATB4 in the electrode for stable power generation. It is concluded that P. otitidis AATB4 can be used as a novel bioelectrogen in microbial fuel cell for sustainable energy production using septic tank wastewater.